Indonesian government's communication messages on Covid-19 in the perspective of intermedia agenda-setting - Rustika Nur Istiqomah,; Atwar Bajari,; Aceng Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The development of media towards digitalization has an impact on every field, including the public communication messages conveyed by the government, especially during the Covid-19 pandemic. It caused various responses from the public. The use of agenda-setting theory is considered quite adaptive in facing the changing times, and even in the digital era like today. This happened to the Indonesian leader who wrote a tweet about the New Normal in several fields as solutions facing the Covid-19 pandemic. Community responses related to Responses to Local Governments, Economic Issues, and Health Protocols were measured by big data analysis by using the IMM system for online media analysis and the ISA system for Twitter analysis. The results show that the intermedia agenda-setting or the transfer of issues from online media to Twitter happened on government public communication messages on the topic of New Normal and vice versa. However, discussions on Twitter about Local Governments led to discussions on online media and reports on Twitter about Economic Issues caused coverage on online media only. Those results had no responses from online media to Twitter. In addition, on the issue of Health Protocol, each agenda on online media and Twitter differed from one another.